The Effect Of Bacillus subtilis Formulation On The Intensity Of Attack Of Bipolaris maydis In Maize (Zea mays L.) - Rasdiana Rasdiana; Amran Muis; Nurlailah Mappanganro; Ramlah Ramlah (Baselang, 2023)
The use of antagonistic microorganisms in controlling plant pathogens is considered an important component in integrated pest control management. The effectiveness of Bacillus subtilis in controlling plant disease-causing pathogens has been widely proven. To simplify application and increase storage time, these bacteria can be formulated in liquid and powder form. This study aims to test the effectiveness of several B. subtilis isolates formulated in powder form to control maize leaf blight. The study was conducted at the Maros Cereal Research Institute. The study was arranged in a completely randomized design consisting of 8 treatments of B. subtilis isolates namely BS-TLB1, BS-BJ6, BS-TM3, BS-TM4, BS -BNt4, BS-BNt5, BS-BNt6, BS-BNt8 and three controls (K1 with the use of synthetic pesticides, K2 with Bipolaris maydis suspension (no formulation) and K3 with no treatment). Parameters observed include the intensity of leaf blight disease which was observed when the plants were 4 MST, 5 MST and 6 MST. The results showed that spraying maize leaves with the B. subtilis formulation had a positive effect on the attack intensity of B. maydis, treatment with BS-BNt4 had the lowest attack intensity, namely 68.00%.